Incidence and Risk Factors of In-Stent Restenosis for Symptomatic Intracranial Atherosclerotic Stenosis: A Systematic Review and Meta-Analysis - Peng, G. (AJNR Am J Neuroradiol, 2020)
BACKGROUND: In-stent restenosis affects long-term outcome in patients with intracranial atherosclerotic stenosis. PURPOSE: The aim of this meta-analysis was to evaluate the incidence and risk factors of in-stent restenosis. DATA SOURCES: All literature that reported in-stent restenosis was searched on PubMed, Ovid EMBASE and Ovid MEDLINE data bases. STUDY SELECTION: Original articles about stents for symptomatic intracranial atherosclerotic stenosis were selected. DATA ANALYSIS: Meta-analysis was conducted to derive the pooled in-stent restenosis using a random-effects model. Meta-regression was performed to explore the risk factors predisposing to in-stent restenosis. DATA SYNTHESIS: In total, 51 studies with 5043 patients were included. The pooled incidence rate of in-stent restenosis was 14.8% (95% CI, 11.9%–17.9%). Among the lesions with in-stent restenosis, 28.8% of them led to (95% CI, 22.0%–36.0%) related neurologic symptoms. The series in the United States had a higher in-stent restenosis rate (27.0%; 95% CI, 20.6%–33.9%) compared with those from Asia (13.6%; 95% CI, 10.3%–17.2%) and other regions as a whole (7.6%; 95% CI, 1.1%–18.1%) (P < .01). Multiregression analysis revealed that younger patient age was related to high in-stent restenosis rates (P = .019), and vertebrobasilar junction location (P = .010) and low residual stenosis (P = .018) were 2 independent risk factors for symptomatic in-stent restenosis rate. LIMITATIONS: The heterogeneity of most outcomes was high. CONCLUSIONS: Our study showed promising results of in-stent restenosis for symptomatic atherosclerotic stenosis. Studies are needed to further expatiate on the mechanisms by which younger patient age, vertebrobasilar junction location, and low residual stenosis could increase in-stent restenosis and symptomatic in-stent restenosis, respectively.